(untitled) ("Journal "U". Economy. Management. Finance.", 2021)
At the present stage of development of the banking system, lending is assigned a large role. Loans make up the majority of the assets of commercial banks and are the first source of additional income. The article reveals the theoretical foundations of the credit process and analyzes the statistical data of VTB Bank (PJSC).